HITRANonline: An online interface and the flexible representation of spectroscopic data in the HITRAN database. (July 2016) - Hill, Christian; Gordon, Iouli E.; Kochanov, Roman V.; Barrett, Lorenzo; Wilzewski, Jonas S.; Rothman, Laurence S.
Abstract: We describe a new, online interface to the HITRAN database that overcomes the many limitations of the existing, 160-character fixed-width, text based format (the ".par" files mostly distributed through an FTP site until now). The interface, called HITRAN online, accesses a relational database [JQSRT 2013:130, 57-61] in which the spectroscopic data are stored in a flexible, extensible and structured format. This allows an arbitrary number of different parameters for each transition to be stored so that HITRAN can represent, for example, non-Voigt line shape profiles as well as parameters representing broadening by species other than "air" and "self". The online interface provides many ways of visualizing data as part of querying the database and allows users to create and save their own output formats to suit their own needs. A bibliography file produced with each data file provides citations and notes to the original data sources to make it easier for users to credit data providers. Once registered with the HITRAN online service, users also have (private) access to thier own search history which summarizes and can repeat queries.